PENGARUH KINERJA KOMUNIKASI DAN IKLIM KOMUNIKASI ORGANISASI TERHADAP PRODUKTIVITAS KERJA BIROKRASI PEMROV DKI JAKARTA : SEBUAH PERBANDINGAN PERSEPSI ATAS KEPEMIMPINAN BASUKI TJAHAYA PURNAMA DAN ANIES BASWEDAN - RIKA IFATI FARIHA,; AG EKA WANATS WURYANTA, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The purpose of this study is to look at the effect of communication performance and organizational climate on the work productivity of DKI Jakarta provincial government bureaucrats, on the leadership of Basuki Tjahaja Purnama (Ahok) and Anies Baswedan. This study uses a survey method and is explanatory. The two leaders were equally unable to raise the work productivity of their employees, but Governor Anies was stronger in creating an organizational communication climate. Meanwhile, Governor Ahok did not change the organizational communication climate at the Bureau of Foreign Cooperation. Correlation test results proved that the value of the variable communication performance with the communication climate of 0.401 with a significance value (sig.) Of 0.010. Judging from the results the value of sig. (0.010 <0.05), it can be said that there is no significant relationship between communication performance variables and communication climate. Meanwhile, the value of the communication performance variable with a communication climate of 0.666 with a significance value (sig.) Of 0.010. Judging from the results the value of sig. (0.000 <0.05), it can be said that there is a significant relationship between the variables of communication performance with the communication climate.